2019 International Conference on Information and Communication Technology Convergence (ICTC) 2019
DOI: 10.1109/ictc46691.2019.8939812
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approach to Remove Ion Interference Effect in Agricultural Nutrient Solutions

Abstract: High concentration agricultural facilities such as vertical farms or plant factories consider hydroponic techniques as optimal solutions. Although closed-system dramatically reduces water consumption and pollution issues, it has ion-ratio related problem. As the root absorbs individual ions with different rate, ion rate in a nutrient solution should be adjusted periodically. But traditional method only considers pH and electrical conductivity to adjust the nutrient solution, leading to ion imbalance and accumu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Our previous work with quadratic regression model [11] was applied on the experiment data for comparison. It failed to remove artifacts and even increased error dramatically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work with quadratic regression model [11] was applied on the experiment data for comparison. It failed to remove artifacts and even increased error dramatically.…”
Section: Resultsmentioning
confidence: 99%
“…Liberti et al provided readjustment method with Gran's plots to remove ion interference effect but it also require prior knowledge of ions. [10] We suggested a machine learning approach to remove the ion interference effect performing 91.5~97.8% accuracy on test cases [11], but failed to remove the artifact from movement of solution. A distorted signal caused by drop of water made the regression fail.…”
Section: Electrode Interferencementioning
confidence: 99%
“…We applied multiple chemicals at same solvent for two reason. At first, we can directly apply machine learning algorithms for removal of ion interference effect [11,12] on the mixture of solutes. Secondly, calibration on the mixture of solutes can reduce the magnitude of artifacts because the ion interference effect is not a random value.…”
Section: B Sensor Arraymentioning
confidence: 99%
“…The magnitude of this artifact was measured as 9~41%. [4] This artifact make ISEbased nutrient management system not feasible for farmers. Kim Hak-Jin et al suggested an ISE-based automated nutrient management system in 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation